Cognitive Constructivism Of Early Childhood Based On Jean Piaget's Thinking - Chitra Charisma Islami; Eva Gustiana (STKIP Muhammadiyah Kuningan, 2021)
In the world of education, Jean Piaget is a figure of constructivism, psychology and epistemology, because as an epistemological figure, Piaget reviews children's ways of thinking to find out about individuals in obtaining knowledge. Piaget put forward the principles and methods are about learning theories that are accepted by educational experts from various countries. The constructivism approach in education is important because the basis for thinking is a contextual approach, little by little knowledge is built, the result of the knowledge that has been built is expanded through a context that is not sudden and limited or narrow. The potential possessed by students requires efforts to maximize so that the provisions that have been set will be in accordance with the learning process. Educators cannot transfer the knowledge contained in the minds of educators as well as students cannot accept the knowledge given, or in other terms transfer knowledge, which means that students must be mentally strong in building knowledge based on their cognitive maturity. Forcing in teaching methods is a very bad thing, because without being forced, students will form the knowledge that has been obtained and learned, the importance of active participation in the learning process. In Piaget's constructivism theory, he found two ways for children to acquire knowledge, namely accommodation and assimilation. The method is one way to achieve what educators want, namely with a comfortable classroom atmosphere so that it raises the motivation of children to be enthusiastic in learning.